Description of Knowledge Legal Aspect of Independent Practice - Wijanarko Heru Pramono; Emilia Puspitasari Sugiyanto; Chandra Hadi Prasetya (Indonesian Journal of Global Health Research, 2023)
Nursing as a medical professional has the right to carry out independent nursing practice. The legal aspects of independent nursing practice are regulated by Indonesian legislation. The knowledge of nurses, especially nurses who carry out independent nursing practices, is different. This knowledge is important to prevent violations of legal aspects. Based on this, the purpose of this study was to find out the description of the legal aspects of independent nursing practice owned by alumni of the DIII Nursing study program who carried out independent nursing practices. The respondents of this study were 5 alumni who had independent nursing practices. This research method is to use qualitative methods with data triangulation analysis methods. The results of the study obtained 6 themes regarding knowledge of the legal aspects of independent nursing practice including licensing, types of services, practice authority, rights and obligations, witnesses, regulatory developments.